2008
DOI: 10.1248/bpb.31.2326
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Fucoidan-Chitosan Hydrogel and Its Application as Burn Healing Accelerator on Rabbits

Abstract: Burn healing includes a specific biological process related to the general phenomenon of growth and regeneration and the primary objective in burn care is the promotion of rapid wound healing with the best functional results. The principal function of a burn dressing is to provide an optimum healing milieu for natural healing and desirable burn dressing may, therefore, be characterized on the basis of its performance such as; (a) provision of adequate gaseous exchange, (b) provision and maintenance of a moist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(98 citation statements)
references
References 45 publications
4
84
1
5
Order By: Relevance
“…Hardness describes the ability to remove the formulation from the container. Low value of hardness is related to the ease of product removal and application but on the contrary, may decrease the retention time at the administration site [40]. In addition, together with the compressibility factor, hardness reflects the applicability to the desired site [41].…”
Section: Viscosity and Mechanical Measurementsmentioning
confidence: 99%
“…Hardness describes the ability to remove the formulation from the container. Low value of hardness is related to the ease of product removal and application but on the contrary, may decrease the retention time at the administration site [40]. In addition, together with the compressibility factor, hardness reflects the applicability to the desired site [41].…”
Section: Viscosity and Mechanical Measurementsmentioning
confidence: 99%
“…Therefore, this study demonstrated apparent anti-bacterial and cutaneous wound healing effects of fucoidan. Fucoidan is known for its anti-bacterial, anti-viral, immunostimulatory, and healing stimulating effects [2][3][4][5][6][7][8][9][10][11]. In a previous study, fucoidan inhibited the growth of Staphylococcus aureus and Escherichia coli [5].…”
Section: Discussionmentioning
confidence: 99%
“…Fucoidan was also used as a prevention and treatment measure to control diseases caused by Helicobacter pylori [4]. Similutaneously, previous liteature demonstrated the cutaneous wound healing effect of fucoidan [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some works published where fucoidan has been used for drug delivery [2,[7][8][9][10][11][12][13], stem cell growth [2], wound healing [2,7,8,14], bone regeneration [2,[15][16][17][18], and in anti-bacterial [19] and cell culture hydrogels [20]. However, compared to the number of reports on the structure and bioactivities of fucoidan, the use of fucoidan in biomedical applications other than as a conventional drug is far less common.…”
Section: Fucoidanmentioning
confidence: 99%